PARIWISATA HALAL SEBAGAI PENUNJANG PARIWISATA DI DESA WISATA MENGGORO - Deliana, Dian (Penerbit Lafadz Jaya, 2023)
Even though Indonesia has a large Muslim population, only a few people are actively involved in the religious tourism industry which is still a topic of interest. Religious tourism has not significantly affected the economy of Menggoro Village. Religious tourism in Indonesia still has a lot of room to be developed so that it can better serve society as a whole. The religious tourism area of Menggoro Tourism Village has a lot of potential to improve the economy of the local community. To maximize the expansion of religious tourism, Menggoro Village can be developed as part of halal tourism. This study aims to determine whether halal tourism has the potential to benefit the local economy or not. The research method is to conduct observations and interviews with the community and tourism village managers who are actively involved in religious tourism. In-depth interviews were conducted with important people who are in charge of the tourism village. According to the findings, making souvenirs, sharia homestays, halal certification for the typical dishes of Menggoro Village, and display areas for original tourism village products can maximize the economic potential of the population. Religious tourism is recognized as superior by the people of Menggoro Village, business owners and tourists.